2021
DOI: 10.1002/nbm.4490
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of physiological and metabolic changes related to isocitrate dehydrogenase 1 mutation expcression by multiparametric MRI and MRS in a rat model with orthotopically grafted human‐derived glioblastoma cell lines

Abstract: The physiological mechanism induced by the isocitrate dehydrogenase 1 (IDH1) mutation, associated with better treatment response in gliomas, remains unknown.The aim of this preclinical study was to characterize the IDH1 mutation through in vivo multiparametric MRI and MRS. Multiparametric MRI, including the measurement of blood flow, vascularity, oxygenation, permeability, and in vivo MRS, was performed on a 4.7 T animal MRI system in rat brains grafted with human-derived glioblastoma U87 cell lines expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…The lower tracer uptake values are consistent with the reduced level of neuroinflammation and by extension the decreased aggressiveness of IDH+ tumors, which is in complete accordance with reports from the literature [ 38 , 42 ]. Our recent study, which investigated multiparametric MRI, also found a spectroscopic profile of lower aggressiveness for IDH+ tumors, which further confirms results obtained in the current study [ 28 ]. Other mechanisms related to the IDH mutation may be suggested albeit based on assumptions that cannot be substantiated from our current data.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The lower tracer uptake values are consistent with the reduced level of neuroinflammation and by extension the decreased aggressiveness of IDH+ tumors, which is in complete accordance with reports from the literature [ 38 , 42 ]. Our recent study, which investigated multiparametric MRI, also found a spectroscopic profile of lower aggressiveness for IDH+ tumors, which further confirms results obtained in the current study [ 28 ]. Other mechanisms related to the IDH mutation may be suggested albeit based on assumptions that cannot be substantiated from our current data.…”
Section: Discussionsupporting
confidence: 92%
“…Blood brain barrier (BBB) penetrance remains an issue for TSPO imaging [ 22 ] but is not a limitation for brain tumors in general or for gliomas per se since the brain blood barrier is disrupted in the vast majority of HGGs. Our previous study showed that contrast-enhancements were observed in our animal models, confirming that the BBB was disrupted [ 28 ]. In any case, our current study underlines the fact that using multiparametric PET, i.e.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations